STRATEGY OF SPIRITUAL AND EDUCATIONAL REFORM IMPLEMENTED IN THE BODIES OF THE INTERNAL AFFAIRS (Scientific journal of the Fergana State University, 2023)
The article scientifically analyzes ideas about the strategy of spiritual and educational reforms implemented in the internal affairs bodies. The article also scientifically substantiates that ensuring a peaceful and peaceful life of the population in our country, the fight against crime and offenses, maintaining public order and security are urgent tasks of state policy today.